The Gilpins and their Fortunes: A Story of Early Days in Australia - Kingston, William Henry Giles, 1814-1880; Webb, Archibald, 1887-1944 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Gilpins and their Fortunes: A Story of Early Days in Australia" by William H. G. Kingston is a historical novel written in the late 19th century. The story follows the Gilpin brothers, Arthur and James, as they emigrate from England to Australia, driven by dreams of a better life. Upon reaching Sydney, they encounter various challenges and adventures that shape their new lives in a rugged and often dangerous landscape. At the start of the narrative, Arthur and James contemplate their futures as they leave their school in England. Soon after arriving in Australia, they heroically save a family from a runaway carriage, earning the attention of a wealthy squatter, Mr. Prentiss, who becomes their ally. The brothers are then appointed as managers of a sheep and cattle station, where they face idleness among certain workers and begin to uncover the shady dealings of the previous manager. As they tackle their new responsibilities, the brothers remain committed to honesty and hard work, setting the stage for their journey through both opportunities and adversity in their venture into the Australian wilderness. (This is an automatically generated summary.)
Release date is 2007-05-15
Produced by Nick Hodson of London, England
Keywords: Christian life -- Juvenile fiction; Australia -- Juvenile fiction; Friendship -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction